Readiness to implement revenue diversification strategies by Malaysian Public Universities / Suhaiza Ismail, Nik Nazli Nik Ahmad and Siti Alawiah Siraj - Ismail, Suhaiza; Nik Ahmad, Nik Nazli; Siraj, Siti Alawiah (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
The objective of this paper is to investigate the factors affecting the readiness (in terms of change commitment and change efficacy) of the public universities in Malaysia to implement revenue diversification strategies. Based on the Weiner’s (2009) Theory of Organisational Readiness for Change, this study used a questionnaire survey to collect data from senior administrators in public universities in Malaysia. A total of 69 completed questionnaires were received. Multiple regression and correlation analyses were used to examine the factors affecting readiness to implement revenue diversification strategies. The results reveal that change valence positively influences change commitment and change efficacy. In addition, task knowledge and resource availability have a significant positive impact on change efficacy and change commitment respectively. This is among the first studies to provide empirical evidence on factors influencing the readiness of universities to adopt revenue diversification strategies to attain financial sustainability, using the Organisational Readiness for Change Theory.